2020
DOI: 10.1093/infdis/jiaa208
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Disease Severity in Children Infected With Respiratory Syncytial Virus: A Systematic Literature Review

Abstract: Background Clinical manifestations of respiratory syncytial virus (RSV) infection vary widely from mild, self-limiting illness to severe life-threatening disease. There are gaps in knowledge of biomarkers to objectively define severe disease and predict clinical outcomes. Methods A systematic search was performed, 1945–March 2019 in databases Ovid Medline, Embase, Global health, Scopus, and Web of Science. Risk of bias was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…TNF-α, IL-6, IL-8, IL-10, IL-13, and IL-33 in children with HRSV were significantly increased in severe infection compared to mild infection (p < 0.05) in children with HRSV. Children with HRSV have higher amounts of IL-8, IFN-a, IL-6, IL-3, IL-33, IL-1a, IL-2, IL-22, G-CSF, CCL-2, and CCL-3, which were associated with children's disease severity [59][60][61]. According to Sheeran et al, all children with HRSV infection had significantly higher levels of IL-6, IL-8, and IL-10 in their nasal wash and tracheal aspirate samples than did control children [62].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α, IL-6, IL-8, IL-10, IL-13, and IL-33 in children with HRSV were significantly increased in severe infection compared to mild infection (p < 0.05) in children with HRSV. Children with HRSV have higher amounts of IL-8, IFN-a, IL-6, IL-3, IL-33, IL-1a, IL-2, IL-22, G-CSF, CCL-2, and CCL-3, which were associated with children's disease severity [59][60][61]. According to Sheeran et al, all children with HRSV infection had significantly higher levels of IL-6, IL-8, and IL-10 in their nasal wash and tracheal aspirate samples than did control children [62].…”
Section: Discussionmentioning
confidence: 99%
“…Jefferies et al [68] designed a clinical trial that integrated omics sciences with the aim of discovering biomarkers of severe acute respiratory tract infection, in infants, due to respiratory syncytial virus and respiratory sequelae [69]. The clinical trial includes an analysis of diverse types of biological samples (nasopharyngeal, blood, buccal, stool, and urine), by genomics, host immune response, transcriptomic, proteomic, metabolomic and epigenomic.…”
Section: Metabolomics Integration With Other Omicsmentioning
confidence: 99%
“…Few studies used concurrent infections such as dengue to identify and evaluate the potential of some biomarkers for severe Pv malaria [ 64 , 65 ]. Other studies showed a good prognostic value of Hp and Lpc-2 to distinguish severe pneumonia due to malaria from those of bacterial and viral origin [ 58 , 66 ], while few studies found CRP to be a good biomarker in the current coronavirus pandemic (COVID-19) [ 67 , 68 ].…”
Section: Sm Biomarkers' Critical Evaluation Challenges and Future Res...mentioning
confidence: 99%